1968
DOI: 10.1021/jo01274a075
|View full text |Cite
|
Sign up to set email alerts
|

Sulfide oxidation with N-halosuccinimides

Abstract: Numerous methods have been developed for the oxidation of sulfides1p2 to sulfoxides in reactions usually giving the sulfoxide contaminated with sulfide and/or sulfone. More recently the use of t-butyl hypochlorite as a reagent for the oxidation of sulfides to sulfoxides has been r e p~r t e d .~,~ These reports prompted us to disclose our results on the use of N-halosuccinimides in methanol as the oxidizing agents. It has been previously shown5 that aromatic sulfides are oxidized cleanly to sulfoxides in aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(26 citation statements)
references
References 0 publications
0
24
0
2
Order By: Relevance
“…It has been previously shown that aromatic sulfides are oxidized cleanly to sulfoxides in aqueous media when treated with NBS. 26,27 Tagaki et al 27 have demonstrated that certain aromatic sulfides could be oxidized to sulfoxides in 70% dioxane-containing water containing NBS in 1964. In addition, Surendra et al's 28 research also demonstrated the oxidation of sulfides to sulfoxides by β-cyclodextrin in water under neutral conditions in 2005.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously shown that aromatic sulfides are oxidized cleanly to sulfoxides in aqueous media when treated with NBS. 26,27 Tagaki et al 27 have demonstrated that certain aromatic sulfides could be oxidized to sulfoxides in 70% dioxane-containing water containing NBS in 1964. In addition, Surendra et al's 28 research also demonstrated the oxidation of sulfides to sulfoxides by β-cyclodextrin in water under neutral conditions in 2005.…”
Section: Resultsmentioning
confidence: 99%
“…A large number of procedures designed for carrying out the oxidation of sulfides to sulfoxides have been published, nevertheless most of them tried in this study resulted in low chemoselectivity and were unable to stop at the sulfoxide oxidation state [7 a-d ]. Most of the reagents tested (m-CPBA, HNO 3 /CH 3 COOH, H 2 O 2 , t-BuOOH/H 2 O/Ti(iPrO) 4 / DET, molybdenum (VI) oxodiperoxo complexes coated on silica gel, N-chloro-succinimide, oxone, MMPP) bore out this limitation [8][9][10] except sodium metaperiodate which reacted with 3-benzylaminoisothiazole (1a) affording 3-benzylaminoisothiazole 1-oxide (2a) in acceptable yields (56%) together with a small amount of 3-benzylaminoisothiazole 1,1-dioxide (3a)(14%) (Scheme 1) [11].…”
Section: Resultsmentioning
confidence: 99%
“…d Analysis by GC-MS confirmed the chlorination of the sulfoxide, but the structure of the particular isomer was not proven. observations of the reactions of sulfides with haloamides [11][12][13] and an N-sulfonyloxaziridine.…”
Section: Reactions In Water-acetonitrile Mixturementioning
confidence: 99%
“…However, reactions E and F with MPS led to almost complete consumption of active chlorine, an observation supported by LC analysis of the dechlorinated glycouril after the reaction. The mechanism of the oxidation of sulfur by haloimides has been described previously 12 as a nucleophilictype attack by the sulfide on the highly positive active chlorine followed by hydrolysis of the chlorosulfonium ion. Our results were consistent with that mechanism, because the weakest nucleophile of the three sulfides, HD, gave the lowest yields of sulfoxide under similar conditions (reactions B, D and F).…”
Section: Stoichiometry and Mechanisms Of Reactionsmentioning
confidence: 99%
See 1 more Smart Citation